2018
DOI: 10.1021/acsami.8b01626
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Ni-Based Magnetic Mesoporous Films as Smart Surfaces for Atomic Layer Deposition: An “All-Chemical” Deposition Approach toward 3D Nanoengineered Composite Layers

Abstract: Mesoporous Ni and Cu-Ni (CuNi and CuNi in at. %) films, showing a three-dimensional (3D) porous structure and tunable magnetic properties, are prepared by electrodeposition from aqueous surfactant solutions using micelles of P-123 triblock copolymer as structure-directing entities. Pores between 5 and 30 nm and dissimilar space arrangements (continuous interconnected networks, circular pores, corrugated mesophases) are obtained depending on the synthetic conditions. X-ray diffraction studies reveal that the Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The codeposition of polymers could benefit the formation of decorated or even mesoporous architectures. Previous studies have demonstrated the codeposition of metals and spherical polymeric micelles present in the electrolyte, which prompted the formation of mesoporous metallic structures following the dissolution of the polymers [ 42 , 43 , 44 ]. After all, the surface charge of polymeric micelles is a key factor for attraction to the working electrode’s surface, as well as for the selection of the system’s constituents.…”
Section: Resultsmentioning
confidence: 99%
“…The codeposition of polymers could benefit the formation of decorated or even mesoporous architectures. Previous studies have demonstrated the codeposition of metals and spherical polymeric micelles present in the electrolyte, which prompted the formation of mesoporous metallic structures following the dissolution of the polymers [ 42 , 43 , 44 ]. After all, the surface charge of polymeric micelles is a key factor for attraction to the working electrode’s surface, as well as for the selection of the system’s constituents.…”
Section: Resultsmentioning
confidence: 99%
“…25 Here, the synthesis of Ni-Pt thin films is accomplished using the well-described mechanism of micelle-assisted electrodeposition to introduce porosity. [26][27][28] In this one-step deposition process, a block copolymer forms micelles when its concentration in water is above the critical micellar concentration (cmc), and the metal ions assemble at the exterior (hydro-philic) part of the micelles. The latter are thus co-deposited when the metal ions are reduced at the working electrode.…”
Section: Introductionmentioning
confidence: 99%
“…A so template consisting of spherical micelles of di-or triblock copolymers (e.g., polystyrene-block-poly(oxyethylene), known as KLE, or poly(ethylene glycol)-block-poly (propylene glycol)-block-poly(ethylene glycol), known as P-123) appears to be more suitable for PN dual-template assisted electrofabrication owing to simultaneous metal deposition and micelle assembly in liquid without involving any gas phase. 12,13 Very recently, we demonstrated the electrodeposition of mesoporous Ni and CuNi lms with tunable pore alignment and morphology from an aqueous surfactant electrolyte using P-123 as the structure-directing entity. 13 P-123 also has been applied to control metal growth inside deep channels of alumina membranes.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Very recently, we demonstrated the electrodeposition of mesoporous Ni and CuNi lms with tunable pore alignment and morphology from an aqueous surfactant electrolyte using P-123 as the structure-directing entity. 13 P-123 also has been applied to control metal growth inside deep channels of alumina membranes. 14 However, instead of forming PNs, nanotube was obtained, due to alumina exhibits outstanding adsorption ability to P-123 micelles.…”
Section: Introductionmentioning
confidence: 99%